Study on water quality of the sungai balok, Gebeng, Kuantan, Malaysia - Mohd Azzre, Sham Mohd Nasir (2017)
The Sungai Balok is one of the rivers in Pahang that has been affected by the human activities around the river vicinity mainly by the industrial estate in Gebeng and indirectly affected by the bauxite mining in Bukit Goh, Kuantan. A study was conducted in order to assess the level of pollution in river water samples based on National Water Quality Standard (NWQS) for Malaysia and Quality Index (WQI) at spatial variation along the river. Four stations were selected from the river and standard method was used for analysis. Water samples were collected at four sampling stations along the Sungai Balok. Water quality was assessed based on physical and chemical parameters. These parameters were pH, dissolved oxygen (DO), temperature, turbidity, total suspended solids (TSS), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammonical nitrogen and selected heavy metals test. The in-situ parameter were DO, temperature, electrical conductivity, turbidity and while the rest of the parameters were analysed in the laboratory. From the results, all parameters were compared to NWQS. The highest average pH value (6.92) was recorded at station 4 in Sungai Balok categorised as class IIB. The DO level showed an average of 5.06 mg/L categorised as class IIB. The BOD values obtained from experiments was ranging between 11 mg/L to 13 mg/L and COD values also high ranging from 14 mg/L to 36 mg/L. Meanwhile the TSS values show a range from 50 mg/L to 62 mg/L which categorised as class III water. The calculation of WQI revealed that the water quality index in Sungai Balok was 57.59 and categorised as class IV. According to NWQS, class IV water can be used as irrigation water. It is proposed that a better regulation needed to be imposed on the surrounding industrial area to prevent a more severe water quality decline in the Sungai Balok. A monthly water quality checks should be performed in the river to monitor the river quality index continuously.